The Effect of Training and Competence on Performance with Workload as an Intervening Variable in Employees of Badan Pendidikan Dan Pelatihan DIY - Fitrianto, Soni; Subyantoro, Arief; Siswanti, Yuni (West Science Journal Economic and Entrepreneurship, 2024)
This research examines the effect of training and competency on performance with workload as an intervening variable for employees of the Badan Pendidikan dan Pelatihan DIY. The study population consisted of 62 permanent Badan Pendidikan Dan Pelatihan DIY employees, with the sample obtained using a total sampling technique. Data was collected through a questionnaire, and data analysis was performed using SEM-PLS. The results show that training and competency positively and significantly affect workload and employee performance. Additionally, the workload variable is an intervening variable between training, competency, and employee performance. The main limitation of this research is its generalizability, as the results apply only to the Badan Pendidikan Dan Pelatihan DIY. It also does not account for other variables and may be affected by respondent subjectivity, as data was collected via a one-time questionnaire with a small sample size. Recommendations for the Badan Pendidikan Dan Pelatihan DIY include improving training quality to enhance employee competency and performance, aligning workload with competency, and conducting training evaluations. Further research should incorporate additional variables, larger sample sizes, and diverse data collection methods and employ a longitudinal design for more in-depth validation and statistical analysis.